Resistance to ethanol sensitization is associated with a loss of synaptic plasticity in the hippocampus. Issue 2 (24th November 2016) - Coune, F.; Silvestre de Ferron, B.; González‐Marín, M.C.; Antol, J.; Naassila, M.; Pierrefiche, O.
Abstract: Behavioral sensitization to repeated ethanol (EtOH) exposure induces an increase in locomotor activity in mice. However, not all animals express such sensitization. Although the literature indicated that the hippocampus may play a role in EtOH sensitization, it is not known whether behavioral sensitization to EtOH is associated with preferential changes in bidirectional synaptic plasticity, i.e., LTP and LTD, two markers of learning capabilities that have also been shown to be involved in addictive behavior. In the present study, we examined whether the vulnerability to develop and express behavioral sensitization to EtOH is associated with altered bidirectional synaptic plasticity in the CA1 area of the dorsal hippocampus. For this purpose, we analyzed both LTP and LTD in resistant and sensitized mice during the expression phase, i.e., 7 days after 10 days of repeated EtOH i.p. administration. We found that resistant mice showed a lack of LTD without changes in LTP. The lack of LTD was associated with an increase in GluN2A protein level and was not due to an altered level of neuronal activity, since no difference was observed between the number of c‐FOS positive neurons in sensitized and resistant mice. Given that both types of synaptic plasticity signals may have distinct roles in specific learning and behaviors, our results suggest that resistant mice could exhibit different phenotypes in terms of learning/memory and addictive behaviors compared to sensitized ones.Synapse 71:e21899, 2017 . © 2016 Wiley Periodicals, Inc. Abstract : Only resistant mice to ethanol locomotor sensitization showed an abolition of hippocampus LTD, accompanied with an upregulation of GluN2A subunit of the NMDA receptor.